Conserving genetic resources of horticultual crops for future - Ganeshan, S (Indian Horticulture, 2019)
The fundamental objective of genetic resources conservation is the maintenance of broad based genetic diversity within each of the species (intra-specific genetic diversity) with a known or potential value in order to ensure availability for exploitation by present and future generations.